2014
DOI: 10.1017/s0950268814003045
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of cattle farmers' perceptions of drivers and barriers to on-farm control of Escherichia coli O157

Abstract: Structural equation modelling and survey data were used to test determinants' influence on farmers' intentions towards Escherichia coli O157 on-farm control. Results suggest that farmers more likely to show willingness to spend money/time or vaccinate to control Escherichia coli O157 are those: who think farmers are most responsible for control; whose income depends more on opening farms to the public; with stronger disease control attitudes; affected by outbreaks; with better knowledge and more informed; with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 22 publications
1
22
0
Order By: Relevance
“…Heffernan et al, 2008 occurrences to be a threat to their farm. In that sense, farmers are more inclined to take additional precautions if they perceive the risk of pathogen introduction onto their farm to be high: for example, if transmission risks are elevated because of disease occurrences in the area (Ekboir, 1999;Garforth et al, 2013;Toma et al, 2013;Toma et al, 2015). Perception of Responsibility.…”
Section: Problem Awareness and Perception Of Responsibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Heffernan et al, 2008 occurrences to be a threat to their farm. In that sense, farmers are more inclined to take additional precautions if they perceive the risk of pathogen introduction onto their farm to be high: for example, if transmission risks are elevated because of disease occurrences in the area (Ekboir, 1999;Garforth et al, 2013;Toma et al, 2013;Toma et al, 2015). Perception of Responsibility.…”
Section: Problem Awareness and Perception Of Responsibilitymentioning
confidence: 99%
“…To take action, farmers need to believe that they are responsible for implementing the management strategies being advocated (Blackstock et al, 2007;Wauters and Rojo Gimeno, 2014; Table 1). For example, cattle farmers' perception of responsibility for Escherichia coli 0157 control was positively associated with their willingness to spend time or money on this issue (Toma et al, 2015). For the majority of farmers enrolled in voluntary Johne's disease programs, concerns about consumer health or consumer perceptions of a link to Crohn's disease were key factors for participation (Sorge et al, 2010a;Nielsen, 2011).…”
Section: Problem Awareness and Perception Of Responsibilitymentioning
confidence: 99%
“…Different studies have identified several psychosocial factors in dairy farmers and veterinarians that might influence their decision on whether or not to implement biosecurity measures. Among these factors, it has been described that the attitude of farmers and veterinarians towards the implementation of biosecurity measures might be affected by the technical knowledge they have (Frössling & Nöremark, ; García & Coelho, ; Toma, Low, Vosough, Matthews, & Stott, ), the individual experiences they have lived (Broughan et al, ), the importance they can attribute to risks (Renault, Humblet, et al, ), and the benefits they can obtain from measures implemented (Ciaravino et al, ). Moreover, their behaviour towards the implementation of biosecurity measures has also been related to their perceived social pressure to apply these measures (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in order for the strategy to 56 be implemented it must be credible to farmers and feasible in their personal context. Even then, many 57 other factors, such as personality, experience, education (Racicot et al, 2012), perceptions, 58 knowledge and attitudes (Toma et al, 2013;Toma et al, 2015) all play a role in determining the likely 59 uptake of advice by farmers. Advice is more likely to be followed if it is tailored to farmers' individualcontexts and characteristics rather than generic (Enticott et al, 2012;Jensen et al, 2016), and 61 negotiated directly with them through a participatory approach (Enticott et al, 2012;Gosling et al, 62 2014; Duval et al, 2016) with veterinarians seen as valuable interpreters of generic advice (Garforth, 63 2015).…”
Section: Introduction 35mentioning
confidence: 99%